2011
DOI: 10.1118/1.3651489
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose reduction to the breast in thoracic CT: Comparison of bismuth shielding, organ‐based tube current modulation, and use of a globally decreased tube current

Abstract: Organ-based TCM produces dose reduction to the breast similar to that achieved with bismuth shielding for both pediatric and adult phantoms. However, organ-based TCM does not affect image noise or CT number accuracy, both of which are adversely affected by bismuth shielding. Alternatively, globally decreasing the tube current can produce the same dose reduction to the breast as bismuth shielding, with a similar noise increase, yet without the streak artifacts and CT number errors caused by the bismuth shields.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
83
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 22 publications
11
83
1
1
Order By: Relevance
“…In a study on a semi-anthropomorphic phantom, Vollmar et al 10 reported a 45% breast dose reduction with this technique,however, the spinal organ dose increased by 19%. Similar results were reported with the organ based tube current modulation technique, yielding 12% to 39% breast dose reduction, based on the size of thorax phantom 11 . Partial CT scanning technique was not available on our scanner.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In a study on a semi-anthropomorphic phantom, Vollmar et al 10 reported a 45% breast dose reduction with this technique,however, the spinal organ dose increased by 19%. Similar results were reported with the organ based tube current modulation technique, yielding 12% to 39% breast dose reduction, based on the size of thorax phantom 11 . Partial CT scanning technique was not available on our scanner.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, the estimated organ dose applied to the female breast decreased by 17.6% to 4.2 mGy in the IRIS group, without inducing streak artifacts reported when using bismuth breast shielding 10,11 and without compromising objective or subjective image quality. This desirable radiation reducing effect is amplified when given the significant proportion of young females undergoing pulmonary MDCTA; overall breast tissue radiosensitivity; as well as the fact that the breast is exposed to the primary beam in virtually all studies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…5,35,46 Several of these studies report significant increases in image noise. 5,35,41 Wang et al 39 showed image noise in both the heart and lung, with increasing noise closer to the shield, where as the study by Einstein et al 44 showed increased noise affecting coronary artery visualisation. Investigators have also reported the presence of undesirable streak and beam hardening artifacts.…”
Section: Image Qualitymentioning
confidence: 98%
“…the Siemens X-CARE. Wang et al (22) showed that organ-based tube current modulation can achieve the same dose reduction as bismuth shielding without introducing artefacts, affecting the CT number accuracy, and increasing image noise.…”
Section: Discussionmentioning
confidence: 99%